Two new fossil species of the genus Atomaria Stephens (Coleoptera: Cryptophagidae) from Eocene European amber with a key to species described from fossil resins - Lyubarsky, Georgy Yu.; Bukejs, Andris (Zootaxa, 2022)
Two new extinct species of the genus Atomaria Stephens, 1829 are described and illustrated: A. (Anchicera) alekseevi sp. nov. from Baltic amber and A. (Anchicera) perkovskyi sp. nov. from Rovno amber. A key to extinct Eocene species of Atomaria is provided.